Self‐reported injury in Australian young adults: demographic and lifestyle predictors - Mark A. Stokes; Sheryl Hemphill; Jane McGillivray; Tracy Evans‐Whipp; Lata Satyen; John W. Toumbourou (Elsevier, 2020)
Abstract Objectives: Injury is the major cause of mortality and morbidity among adolescents and young adults. This study examined the use of injury self‐reports and various causes of injury among adolescents. Methods: A cohort recruited in 2002 as a representative sample of students from the State of Victoria in south‐east Australia was followed and resurveyed in young adulthood in 2010 (mean age 21.0) and 2012 (mean age 23.1) with 75% of the target sample retained (N=2,154, 55.8% female). Results: Prior injuries were reported by 55.5% in 2010 and 54.6% in 2012, leaving 18% with continuing disability. Reported causes of injury in 2012 were sports (55.1%) and alcohol use (9.7%). Logistic regression revealed that injury in 2012 was predicted by rural school attendance in 2002 (Adjusted Odds Ratio [OR] 1.4 CI 1.1-1.7) and in 2010 by male gender (OR 2.2, CI 1.8-2.6), reported self‐harm (OR 1.6 CI 1.1-2.2), and unemployment (OR 0.7, CI 0.5-1.0). Conclusions: Self‐reported injury among young adults is reliably reported, and suggests the need to further examine gender, rural communities and self‐harm, and indicates modifiable contributors to injury. Implications for public health: Modifiable contributors to injury prevention are revealed as work environment, sports participation and alcohol use.